INTRODUCTION - G Van der Watt (Acta Theologica)
At the end of 2019, Prof. Pieter Verster officially retires as Professor in the Department of Practical and Missional Theology of the Faculty of Theology and Religion, University of the Free State. Since 1981, he has been a minister of the Word of God in the Dutch Reformed Church; since 1992, he has been lecturer and, from 1997, Professor in Missiology. He has had an outstanding academic career. In recognising his academic contribution, acclaiming his dedication to the formation of students and in appreciating him as colleague and loyal friend, it has been decided to dedicate this Acta Theologica Supplementum edition as Festschrift in honour of him.